Pursuit of Moksha through Existential Anxiety and Karma in Ghanashyam Khadka’s Nirvana - Chalise, Keshav Raj (The Outlook: Journal of English Studies, 2022)
The idea of struggle for existence is always the turning point for the search for ultimate reality. Reality leads to realization. Moksha is the point of ultimate realization. Based on the theme of Moksha, the novel Nirvana by Ghanashyam Khadka proposes a new mode of defining and exemplifying the process of Moksha. This study explores how the transitoriness in life and the realization of meaninglessness in life have conditioned us to accept every dimension of Dukha, which ultimately leads us to enlightenment and Nirvana. Grounded on the principles of existential anxiety and the search for Moksha through Gita philosophy, this study examines how the queries on the truth of life and death lead to the realization of the value of death in life. These queries are meant for existence and they properly lead to the level of Moksha. Before knowing the truth of human limitation to the knowledge of worldly existence and life, human beings are disturbed by the destined events of life, but these events become the sources of the perfect knowledge to enable one to be free from all worldly sorrows and pains. The experience of sadness and loneliness in life makes people think that they should give up anger and malice on the journey of life to understanding the truth, the Moksha. The novel, Nirvana, shows the central characters, Monika and the narrator, undergoing long troubles of life individually, have realized ultimate peace when they have followed Buddhist meditation in search of Nirvana, but throughout their life, they are guided by the Gita theory of Karma and essence.